The Implementation of Team Games Tournament Learning Model to The Volleyball Play Technique in Randudongkal Junior High School - Jati, Agus Wahyu Kusuma; Hidayah, Taufiq; Wahyudi, Agung (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This research aims to determine the implementation of Cooperative Learning Model, type Team Games Tournament (TGT) to the volleyball game for lower passing technique and lower service technique of Junior High School students in Randudongkal Rayon, Pemalang Regency. The method used in this study is the action research method, with data collection techniques using closed observations with scale responses to teacher teaching activities. The scale of the answers in this study uses a modified Likert scale, where each answer has the same intensity. Teaching activities are conducted in two meetings, with learning steps as follows: the teacher conveys the learning objectives, motivates students and links the lesson with the previous ones, the teacher organizes students into small groups (4-6 students) and discusses the subject matter, the teacher calls the group representatives to be in front of the class and gives questions to answer, the teacher divides students into the tournament chart and shares tournament questions based on the level of difficulty, the teacher gives awards to each group that has high scores. The participants in this study were eight junior high school teachers in Rayon Randudongkal with a random sampling technique. The results of the study stated that teachers in Randudongkal rayon were still less able to apply the cooperative learning model type Team Games Tournament (TGT) on lower passing technique and lower service technique for the volleyball game of junior high school students in Randudongkal District.